Knowledge of Tuberculosis among Tuberculosis Patients Attending Federal Medical Centre, Owo, Ondo State, Nigeria - Akorede, Seun Nurudeen; Ajayi, Ayodotun Edward; Tawose, Peter Oluwatimilehin (Unnes Journal of Public Health, 2021)
Globally, tuberculosis (TB) constitutes a significant public health emergency. Despite the downward trend in TB incidence and prevalence, every continent still reports new cases, especially Africa and south-east Asia (WHO, 2012). This study aimed to investigate the signs, symptoms, transmission mode, and knowledge of tuberculosis (TB) among tuberculosis patients attending Federal Medical Centre, Owo, Ondo State Nigeria. A descriptive survey design was adopted, while sample population comprised of all the aforementioned tuberculosis patients. About 151 persons were selected using Multistage sampling procedure. A closed-ended questionnaire collection was used for data collection and the instrument was validated by experts with ascertained reliability. The data were then subjected to statistical analysis of Cronbach's alpha, and a correlation coefficient of 0.76 was obtained. Conclusively, the patients have knowledge of TB signs and symptoms as well as transmission mode. Therefore, this knowledge is recommended to be sustained among the patients. Multistage sampling procedure was used to select one hundred and fifty-one (151) a researcher’s designed closed-ended questionnaire was used for data collection. The instrument was validated by experts with reliability ascertained. The data obtained were subjected to statistical analysis of Cronbach alpha and a correlation coefficient of 0.76 was obtained. The findings reveals that: Tuberculosis patients have knowledge of signs and symptoms of TB, Tuberculosis patients have knowledge of mode of transmission of TB Therefore, the study concluded that tuberculosis patients have knowledge of mode of transmission, signs and symptoms of TB. Therefore, it is recommended that the knowledge of mode of transmission and symptoms of TB should be sustained among the patients.